Ring-closing olefin metathesis for the synthesis of phosphorus containing heterocycles - Hetherington, L; Greedy, B; Gouverneur, V (2000)
A series of cyclic phosphorus containing heterocycles 9a-k was prepared in a one-step procedure by ring closing metathesis of dienes 7a-k. (C) 2000 Elsevier Science Ltd.